2004
DOI: 10.1507/endocrj.51.499
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Diabetic Nephropathy Enhances the Plasma Osteopontin Level in Type 2 Diabetic Patients

Abstract: Abstract. Osteopontin (OPN) is thought to play multiple roles in the progression of atherosclerotic plaque including diabetic vascular complications. However, it still remains unclear whether the level of OPN in vivo is indeed clinically associated with the progression of diabetic complications. This study evaluated whether the levels of OPN in plasma and urine are correlated with the progression of diabetic complications, such as retinopathy, neuropathy, and nephropathy in patients with type 2 diabetes. In 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
40
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 33 publications
5
40
1
Order By: Relevance
“…Similarly, expression of the gene encoding osteopontin was decreased in diabetic mice treated with avosentan. Osteopontin has been identified as a marker of mesangial expansion in the diabetic mouse kidney [29], the severity of diabetic nephropathy in patients [30] and development of atherosclerosis [31]. The decrease in osteopontin expression with avosentan treatment is therefore consistent with decreases in the expression of genes encoding AT1a, TGF-β and NF-κB p65 subunit, which stimulate and are stimulated by osteopontin [32].…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, expression of the gene encoding osteopontin was decreased in diabetic mice treated with avosentan. Osteopontin has been identified as a marker of mesangial expansion in the diabetic mouse kidney [29], the severity of diabetic nephropathy in patients [30] and development of atherosclerosis [31]. The decrease in osteopontin expression with avosentan treatment is therefore consistent with decreases in the expression of genes encoding AT1a, TGF-β and NF-κB p65 subunit, which stimulate and are stimulated by osteopontin [32].…”
Section: Discussionmentioning
confidence: 88%
“…In humans, the plasma OPN level is significantly correlated with the extent of coronary atherosclerosis. 7,8 Moreover, the OPN levels are particularly elevated in patients with type 2 diabetes, 9,10 and we showed that peroxisome proliferator-activated receptor a ligands suppress OPN expression in macrophages in vitro and that bezafibrate reduces plasma OPN levels in patients with type 2 diabetes. 11 These clinical studies provide evidence that OPN may play a causal role in the development of cardiovascular disease in humans.…”
mentioning
confidence: 72%
“…31,32 OPN is a proinflammatory cytokine implicated in the chemoattraction of monocytes and development of diabetic nephropathy, 16,17 and its levels are significantly elevated in patients with diabetic nephropathy. 9,33 OPN transcription is induced in response to high glucose, 34 raising the possibility that increased OPN secretion in diabetes may play a direct causal role in the development of diabetic nephropathy. For many years, it has been well known that OPN is upregulated in the interstitium, especially the proximal tubules, in the diabetic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…However, OPN was originally found in bone and shown to regulate the formation and calcification of bone tissue (7). Notably, OPN has also been linked to vascular remodelling and calcification, especially in diabetic arteries (8), and has been shown to associate with diabetic retinopathy (9) and nephropathy (10) in patients with type 2 diabetes (T2D), as well as cardiovascular disease (CVD) events in nondiabetic subjects with a history of coronary artery disease (CAD) (11). However, its role for late complications in patients with type 1 diabetes (T1D) is not known.…”
mentioning
confidence: 99%